Differences in folate production by bifidobacteria of different origins - SUGAHARA, Hirosuke (Biosci Microbiota Food Health, 2015)
Bifidobacteria are known to produce folate, a vital nutrient for humans. Previous studies have suggested that the ability to produce folate is strain dependent, but further adequate evaluation is needed. In this study, a total of 44 strains, including 12 species and 7 subspecies, of bifidobacteria were investigated for the production of folate during cultivation in medium containing essential levels of folate for growth of the tested strains. An in vitro assay showed that all strains of human-residential bifidobacteria (HRB) were able to produce folate, whereas most strains of non-HRB were not, with the exception of the B. thermophilum and B. longum ssp. suis strains. The differences in the in vivo production of folate by HRB and non-HRB were confirmed using mono-associated mice. The fecal folate concentrations, blood levels of hemoglobin and mean corpuscular volumes were significantly higher in the mice colonized with a folate producer, B. longum subsp. longum, compared with mice colonized with a nonproducer, B. animalis subsp. lactis. Our results confirmed the differences in folate production between HRB and non-HRB strains and suggested the benefit of HRB to hosts from the perspective of potential folate delivery.